Drug-resistant epilepsy in children under 14 years: clinical and epidemiological characteristics at a tertiary hospital in Lima, Peru - Espinoza-Quinteros, Ivan (2025)
Objective: To determine the frequency and clinical characteristics of children with drug-resistant epilepsy treated at a national hospital in Lima, Peru. Materials and methods: A prospective, case-series study was conducted on patients under 14 years of age with drug-resistant epilepsy, treated between October 2013 and March 2014. Drug resistance was defined as the persistence of seizures despite the use of at least two antiepileptic drug regimens at maximum tolerated doses. Data were collected through interviews with family members and a review of medical records. Results: Forty-six patients were enrolled, representing 26.0 % of children under 14 years of age treated for epilepsy. The mean age was 8.46 ± 3.55 years, with 42.6 % of patients being female. The median age at seizure onset was 10.3 months, and the average duration of epilepsy was 6.5 years. Most patients (66 %) had symptomatic or cryptogenic epilepsy, with brain malformations and postnatal infections being the most common causes (14.9 % each). A total of 17 % of the patients were diagnosed with idiopathic epilepsy. The most common types of epilepsy were focal epilepsy not otherwise specified (42.6 %) and generalized epilepsy not otherwise specified (17 %), followed by Lennox-Gastaut syndrome (14.9 %). Regarding antiepileptic treatment, 51.1 % were receiving dual therapy and 21.3 % were on triple therapy. Additionally, 89.4 % had learning disorders and 85.1 % had intellectual disability. Among children over 3 years old, 37.5 % were not attending school. 19.1 % were hospitalized at least once in the past year, with an average hospitalization duration of 20.1 days. Conclusions: Drug-resistant epilepsy has a significant impact on the health and quality of life of children, creating a substantial burden on the healthcare system. Improving access to specialized treatments and comprehensive patient management is essential.